Sepsis-associated acute kidney injury: A bibliometric analysis of the global research output and collaboration network (2013-2023) - Minhui Yin; Qinlan Hou; Chunlin Zhu; Shuangping Zhao (Journal of Acute Disease)
Objective: To explore the current status of sepsis-associated acute kidney injury (SA-AKI) research and predict its future research directions. Methods: The bibliometric overview of publications was conducted in the field of SA-AKI based on Web of Science Core Collection database from January 2013 to August 2023. This study employed software such as CiteSpace and VOSviewer to conduct bibliometric and visualization analysis of the included literature, including publication trends, geographic distribution characteristics, author contributions, citations, funding sources characteristics, and keyword clustering. Results: A total of 6509 articles were analyzed, and the number of publications and citations increased from 2013 to 2022. The United States had the highest number of publications in SA-AKI, while France was the country with the highest number of citations per publication. Keyword clustering analysis showed that the pathophysiology and definition of SA-AKI were the research focus, and the research hotspots were "machine learning", "vitamin C", "kinase", "hemodynamics", "renal microcirculation" and "mitochondria". Literature coupling analysis indicated that exploring the management and treatment of SA-AKI was the research frontier. Conclusions: Over the past decade, SA-AKI research has shown a upward trend in terms of the number of publication. Research primarily focuses on exploring mechanisms and improving early warning systems. Mechanisms involve microcirculatory dysfunction, inflammation, and other pathophysiological factors. Future recommendations include continuing basic research, achieving clinical application of novel biomarkers, and prioritizing renal recovery mechanisms in treatment strategies.